2019
DOI: 10.1038/s41598-019-50331-9
|View full text |Cite
|
Sign up to set email alerts
|

TaAPO-A1, an ortholog of rice ABERRANT PANICLE ORGANIZATION 1, is associated with total spikelet number per spike in elite European hexaploid winter wheat (Triticum aestivum L.) varieties

Abstract: We dissected the genetic basis of total spikelet number (TSN) along with other traits, viz. spike length (SL) and flowering time (FT) in a panel of 518 elite European winter wheat varieties. Genome-wide association studies (GWAS) based on 39,908 SNP markers revealed highly significant quantitative trait loci (QTL) for TSN on chromosomes 2D, 7A, and 7B, for SL on 5A, and FT on 2D, with 2D-QTL being the functional marker for the gene Ppd-D1. The physical region of the 7A-QTL for TSN revealed the presence of a wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 52 publications
5
52
0
Order By: Relevance
“…To analyze the two physical regions, we used a similar strategy, as described in Muqaddasi et al 50 . More specifically, ~ 2-Mb (1-Mb upstream and downstream) wheat reference genomic sequence around the most significant markers was retrieved to characterize the QTL physical region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the two physical regions, we used a similar strategy, as described in Muqaddasi et al 50 . More specifically, ~ 2-Mb (1-Mb upstream and downstream) wheat reference genomic sequence around the most significant markers was retrieved to characterize the QTL physical region.…”
Section: Resultsmentioning
confidence: 99%
“…As previously used to investigate the genetic basis of total spikelet number 50 and suggested by Borril et al 58 , the availability of high-quality assemblies of cultivars makes it possible to explore the physical regions associated with the MTA. We analyzed the haplotype structure and the nucleotide diversity of high-confidence genes annotated in an interval of 2-Mb around the most significant markers of QGpc.ipk-2B and QGpc.ipk-6A .…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, grain yield represents the culmination of many genetic, developmental, and environmental interactions with the coordination of plant growth and development across the growing season, and is under complex genetic control—although it can often show high heritability (e.g. Muqaddasi et al 2019 ). Yield can be largely partitioned into three major components: grain weight/size and shape, grain number per spike and spike number per unit area (Gegas et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, numerous natural genetic variants controlling yield components have been map-based cloned in the diploid cereal crop rice ( Oryza sativa L.) (for a review of rice grain size genes, see Li et al 2018a ), and these tend to account for ~ 10–40% of the phenotypic variation. In contrast, while exceptions do exist, most notably a locus on chromosome 7A controlling spikelet number per ear (Muqaddasi et al 2019 ; Kuzay et al 2019 ; Voss-Fels et al 2019 ), natural variation at wheat genetic loci controlling yield and yield component traits in bread wheat typically control just ~ 2–10% of the variation (reviewed by Brinton and Uauy, 2019 ). This observation is likely due to the compensatory effects of homoeologous genes in polyploid wheat.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that APO1 and APO2 physically associate with an E3 ubiquitin ligase, LARGE2, to regulate panicle size and grain number, suggesting a promising module of LARGE2-APO1/APO2 for yield improvement in crops (Figure 3) [131]. Wheat TaAPO-A1, an ortholog of rice APO1, is crucial for the total spikelet number determination, suggesting the conserved nature of this gene across grass species [132]. Rice TAW1 (TAWAWA1) encodes a nuclear protein and acts the upstream of SVP MADS-box genes to fine-tune the timing when meristems acquire the determinant spikelet phase.…”
Section: Other Key Regulators/modules Involved In Bm and Sm Identifymentioning
confidence: 99%